A Janus Nickel Cobalt Phosphide Catalyst for High‐Efficiency Neutral‐pH Water Splitting - Wu, Rui; Xiao, Bing; Gao, Qiang; Zheng, Ya‐Rong; Zheng, Xu‐Sheng; Zhu, Jun‐Fa; Gao, Min‐Rui; Yu, Shu‐Hong (Angewandte Chemie International Edition, 2018)
Transition‐metal phosphides have stimulated great interest as catalysts to drive the hydrogen evolution reaction (HER), but their use as bifunctional catalytic electrodes that enable efficient neutral‐pH water splitting has rarely been achieved. Herein, we report the synthesis of ternary Ni0.1Co0.9P porous nanosheets onto conductive carbon fiber paper that can efficiently and robustly catalyze both the HER and water oxidation in 1 m phosphate buffer (PBS; pH 7) electrolyte under ambient conditions. A water electrolysis cell comprising the Ni0.1Co0.9P electrodes demonstrates remarkable activity and stability for the electrochemical splitting of neutral‐pH water. We attribute this performance to the new ternary Ni0.1Co0.9P structure with porous surfaces and favorable electronic states resulting from the synergistic interplay between nickel and cobalt. Ternary metal phosphides hold promise as efficient and low‐cost catalysts for neutral‐pH water splitting devices. Sheets and paper: Ternary Ni0.1Co0.9P porous nanosheets anchored onto conductive carbon fiber paper, can be used as a bifunctional catalytic material for driving both water reduction and oxidation reactions efficiently in neutral‐pH electrolyte under ambient conditions.